Analisis Manajemen Resiko Pelaksanaan Kegiatan Penyusunan Data Statistik Dan Informasi Dinas Perkebunan Provsu - Dalimunthe, Afifah; Harahap, Muhammad Ikhsan (Universitas Labuhanbatu, 2021)
The Plantation Service has the task of recognizing the administration of local government/state authorities in the fields of plantation production, plantation protection, plantation management, plantation management tools, and supporting tasks. The Plantation Service is an element of regional autonomy for the state government and is led by a Head of Service who reports to the governor and is responsible to the governor through the state secretary. The implementation of these activities is certainly not without problems. The most common problems are delays and non-execution of planned activities. However, risks can be unpredictable and unpredictable. These risks can be managed by identifying and quantifying the risks that may occur. The purpose of this study is to determine the various risks in carrying out activities to prepare statistical data and information, as well as determine the value that will be realized after being identified based on the potential and magnitude of the impact. The analytical method used is a descriptive qualitative approach. The research method used in this survey is a qualitative survey which describes statistical data on the implementation and editing activities of plantation information in 2020 data (n-1), and financial data is explained by qualitative explanations. As a result of this research, each element of risk should be assigned to the party who has the best control over the risk. In other words, 1) the district and Manban plantation statistics coordinators do not change every year, so they are easy to learn. Plantation data. 2) Organization of more intense socialization. 3) Human resource development. District statistician in charge of plantations.